2021
DOI: 10.1111/cas.14905
|View full text |Cite
|
Sign up to set email alerts
|

CDKN1C‐mediated growth inhibition by an EZH1/2 dual inhibitor overcomes resistance of mantle cell lymphoma to ibrutinib

Abstract: Mantle cell lymphoma (MCL) is a malignancy with poor prognosis and comprises about 3% of non-Hodgkin's lymphoma (NHL). 1 In the majority of cases, the molecular mechanism initiating MCL is the t(11:14)(q13;q32) translocation resulting in overexpression of cyclin D1 driven by the immunoglobulin heavy chain locus. 2,3 Subsequently, secondary genetic alterations in pathways, such as CDKN2A/CDK4/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Valemetostat is a dual inhibitor of EZH1 and EZH2 that prevents trimethylation of H3K27, leading to altered gene expression patterns, which suppresses proliferation of EZH1/2-dependent cancer cells. Compared with established EZH2-specific inhibitors (GSK126), dual EZH1 and EZH2 inhibitors showed a significantly stronger reduction in H3K27me3 levels [ 12 , 39 ]. In an ongoing open-label phase 1 study (NCT 02732275, 2 November 2020 data cut-off) evaluating valemetostat tosylate monotherapy, the objective response rate (ORR) was 55.6% in 45 relapsed/refractory (r/r) PTCL patients and 50% in 14 r/r adult T-cell leukemia/lymphoma (ATL) patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Valemetostat is a dual inhibitor of EZH1 and EZH2 that prevents trimethylation of H3K27, leading to altered gene expression patterns, which suppresses proliferation of EZH1/2-dependent cancer cells. Compared with established EZH2-specific inhibitors (GSK126), dual EZH1 and EZH2 inhibitors showed a significantly stronger reduction in H3K27me3 levels [ 12 , 39 ]. In an ongoing open-label phase 1 study (NCT 02732275, 2 November 2020 data cut-off) evaluating valemetostat tosylate monotherapy, the objective response rate (ORR) was 55.6% in 45 relapsed/refractory (r/r) PTCL patients and 50% in 14 r/r adult T-cell leukemia/lymphoma (ATL) patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although GSK126 has progressed to a phase 1 clinical trial (NCT02082977), of the 22 enrolled patients with relapsed DLBCL, solid tumours, and other non-Hodgkin lymphomas, only one patient had a partial response, and seven remained stable [18]. Compared with GSK126, which inhibits only EZH2, OR-S1 is a novel dual inhibitor of EZH1 and EZH2 that fully impairs PRC2 activity and has higher anti-tumour activity than that of GSK126 in acute myeloid leukaemia, DLBCL, and mantle cell lymphoma (MCL) cells [18,19]. OR-S1 promotes quiescence in cancer cells by upregulating CDKN1C, which encodes p57 and blocks Rb phosphorylation.…”
Section: Gsk126 Or-s1mentioning
confidence: 99%
“…After treatment of mice bearing MCL patient-derived xenografts with the new MCL drug ibrutinib, the tumour size has been found to reach nearly 40,000 mm 3 . Although one study has found that OR-S1 suppresses almost 90% of tumour growth, the treated mice survived only until study completion [19]. Despite its potential to induce quiescence in cancer cells and its in vivo tolerability, OR-S1 has yet to be clinically tested.…”
Section: Gsk126 Or-s1mentioning
confidence: 99%
“…Kagiyama et al assessed the effect of a novel EZH1/2 dual inhibitor, named OR-S1, a close analog of valemetostat, also known as DS-3201 or (R)-OR-S2, on MCL tumor growth (139).…”
Section: Valemetostatmentioning
confidence: 99%